Towards a Framework for Ontology-Based Data Access: Materialization of OWL Ontologies From Relational Databases - Gómez, Sergio Alejandro (2018)
The landscape of information systems applications is comprised of legacy components that many times rely on heterogeneous data sources, proprietary data formats, and a low-level knowledge representation. Only seasoned programmers who maintain those systems may interpret these data. Ontology-based Data Access is a novel approach for developing information systems where an ontology defines a high-level global schema of already existing data sources and provides a vocabulary for user queries. In this work, we report on the construction of a system that exports such data, represented as a legacy relational database, as an OWL ontology in accordance to the W3C Direct Mapping specification. We discuss several case studies that show how the proposed application works.